Sediment budget controls on foredune height: Comparing simulation model results with field data. Issue 9 (1st April 2018) - Davidson‐Arnott, Robin; Hesp, Patrick; Ollerhead, Jeff; Walker, Ian; Bauer, Bernard; Delgado‐Fernandez, Irene; Smyth, Thomas
Abstract: The form, height and volume of coastal foredunes reflects the long‐term interaction of a suite of nearshore and aeolian processes that control the amount of sand delivered to the foredune from the beach versus the amount removed or carried inland. In this paper, the morphological evolution of more than six decades is used to inform the development of a simple computer model that simulates foredune growth. The suggestion by others that increased steepness of the seaward slope will retard sediment supply from the beach to the foredune due to development of a flow stagnation zone in front of the foredune, hence limiting foredune growth, was examined. Our long‐term data demonstrate that sediment can be transferred from the beach to the foredune, even with a steep foredune stoss slope, primarily because much of the sediment transfer takes place under oblique rather than onshore winds. During such conditions, the apparent aspect ratio of the dune to the oncoming flow is less steep and conditions are not as favourable for the formation of a stagnation zone. The model shows that the rate of growth in foredune height varies as a function of sediment input from the beach and erosion due to storm events, as expected, but it also demonstrates that the rate of growth in foredune height per unit volume increase will decrease over time, which gives the perception of an equilibrium height having been reached asymptotically. As the foredune grows in size, an increasing volume of sediment is needed to yield a unit increase in height, therefore the apparent growth rate appears to slow. Copyright © 2018 John Wiley & Sons, Ltd. Abstract : Since it was initiated 80 years ago this 10 m high, steep foredune has been growing continuously in height and width, and is increasing in height today at a rate of about 1 m per decade. This empirical evidence and results from a computer simulation model show that a steep seaward slope does not cutoff sand supply for dune growth and that foredunes can potentially increase in height indefinitely.